2015
DOI: 10.1007/s10295-015-1601-1
|View full text |Cite
|
Sign up to set email alerts
|

Concentration- and roughness-dependent antibacterial and antifungal activities of CuO thin films and their Cu ion cytotoxicity and elution behavior

Abstract: In this study, we aimed to evaluate the antibacterial and antifungal properties, cytotoxicity, and elution behavior of copper oxide (CuO) thin films with varying concentrations and roughness values. CuO films greater than 0.2 mol % showed 99.9 % antimicrobial activity against Escherichia coli, Staphylococcus aureus, Campylobacter jejuni, and Penicillium funiculosum. Cu ions were found to be noncytotoxic in New Zealand white rabbits. The concentration of Cu ions from CuO thin films eluted in drinking water in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Last but not the least, although it was only the antibacterial efficiency against E. coli that was investigated in the present study, copper surfaces have actually shown capability against a very broad range of bacteria [3,7,52], viruses [53][54][55], and fungi [25,52,56]. Therefore, the strategy proposed here is also encouraging in many scenarios where the general antimicrobial property is needed.…”
Section: Discussion On This Promising Strategy and Practical Insightsmentioning
confidence: 78%
See 1 more Smart Citation
“…Last but not the least, although it was only the antibacterial efficiency against E. coli that was investigated in the present study, copper surfaces have actually shown capability against a very broad range of bacteria [3,7,52], viruses [53][54][55], and fungi [25,52,56]. Therefore, the strategy proposed here is also encouraging in many scenarios where the general antimicrobial property is needed.…”
Section: Discussion On This Promising Strategy and Practical Insightsmentioning
confidence: 78%
“…Copper oxide surfaces with antibacterial activity have been successfully synthesised by various methods, e.g. chemical vapour deposition [20], sputtering [21], wet chemical method [23], hydrothermal method [24], and spin coating [25].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%